Multiple access schemes for Ethernet Passive Optical Networks (EPONS) - Zhu, Yongqing (2008)
This thesis has proposed several novel bandwidth allocation schemes for upstream transmissions in Ethernet Passive Optical Networks (EPONs). It also presents various solutions to support DiffServ and provide fair scheduling based on the proposed schemes. Furthermore, the mathematical models have been developed to evaluate the performance of the proposed schemes.